2022
DOI: 10.1111/coa.13950
|View full text |Cite
|
Sign up to set email alerts
|

Early hearing loss detection in gout using extended high frequency audiometry

Abstract: Objective The study aimed to analyse the hearing levels of patients with gout using extended high frequencies (EHFs) audiometry. Thus, we aimed to reveal the early detectability of potential hearing losses. Design Comparative cross‐sectional study. Settings A single centre patient was diagnosed with gout disease. Participants Two groups consisted of 32 patients with gout and 32 healthy volunteers. Main Outcome Measures The primary outcome was hearing thresholds in pure tone (PT) audiometry and EHFs audiometry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Galarza‐Delgado et al found extended high frequencies to be more selectively affected by rheumatoid arthritis‐associated hearing loss, with 94.9% of patients exhibiting hearing loss at 10–16 kHz compared with 36.8% at 0.5–3 kHz and 68.4% at 4–8 kHz 17 . Sahin et al showed EHF hearing thresholds to be significantly higher in patients with gout compared with controls at all frequencies studied 18 . In Lasso de la Vega et al series, EHF testing more than doubled the number of patients with systemic lupus erythematosus that would be diagnosed with hearing loss (70% based on EHF vs. 30.9% based on conventional audiometry) 19 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Galarza‐Delgado et al found extended high frequencies to be more selectively affected by rheumatoid arthritis‐associated hearing loss, with 94.9% of patients exhibiting hearing loss at 10–16 kHz compared with 36.8% at 0.5–3 kHz and 68.4% at 4–8 kHz 17 . Sahin et al showed EHF hearing thresholds to be significantly higher in patients with gout compared with controls at all frequencies studied 18 . In Lasso de la Vega et al series, EHF testing more than doubled the number of patients with systemic lupus erythematosus that would be diagnosed with hearing loss (70% based on EHF vs. 30.9% based on conventional audiometry) 19 …”
Section: Discussionmentioning
confidence: 97%
“…17 Sahin et al showed EHF hearing thresholds to be significantly higher in patients with gout compared with controls at all frequencies studied. 18 In Lasso de la Vega et al series, EHF testing more than doubled the 19 Although the aforementioned series can point to an etiology of hearing loss, it is often less clear. Main theories for "hidden hearing loss" include noise exposure, aging, peripheral neuropathy, and ototoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…It corresponded well with a previous study reporting significant abnormalities in otoacoustic emissions at higher frequencies (4 and 5 kHz) in participants with hyperuricemia [ 30 ]. High-frequency hearing loss has been detected in patients with gout [ 31 ]. Considering that microvascular degenerative diseases with various etiologies can cause cochlear dysfunction, especially in high-frequency bands of the cochlea [ 32 , 33 , 34 ], our results might shed additional light on the association between hyperuricemia and high-frequency hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Research delineates distinct associations among hearing loss, gout, and serum urate levels. [11,12] Nonetheless, the elucidation of these relationships through conventional epidemiological approaches is obfuscated by potential confounders, including pain, comorbidities, and issues of reverse causality. [13] Mendelian randomization (MR) embodies a genetic instrumental approach to causal inference.…”
Section: Introductionmentioning
confidence: 99%